Associations between design professionals working on computers and risks of musculoskeletal diseases: A systematic review - Mohd Juzad, Kodsiah; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; Ab. Rahman, Rozanah (Universiti Putra Malaysia, 2021)
Introduction: This systematic review emphasises on the risk factors of musculoskeletal diseases (MSDs) among design professionals such as designers and architects due to long hours of working in front of computers. Aims: This study aimed to identify MSDs and its associated factors among design professionals such as designers and architects who relied heavily on computers to complete their design tasks. Methods: This review adopted the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guideline. Two databases namely Scopus and PubMed were searched. Results: The systematic search retrieved 16 articles for analysis. Four main themes emerged from the thematical analysis, namely computer usage risk, computer mouse risk, body posture and anthropometric as well as risk assessment. A total of 11 sub-themes were formulated based on the four main themes. Conclusion: Long hours spent with the computer increased the risk of MSDs and design professional users were found to spend more hours working on the computer compared to office workers and students. As an intense computer user, mouse usage and unergonomic workstation were identified associated with MSDs risk among design professionals based on various MSDs assessment. The systematic review suggested future compressive studies among design professionals such as designers, design engineers and architects on MSDs risk due to lack of previous research on this intense computer user group.